PP.27.10: RELATIONSHIP BETWEEN MICROVASCULAR T REGULATORY LYMPHOCYTES AND CIRCULATING LYMPHOCYTES. (June 2015) - De Ciuceis, C.; Rossini, C.; Airò, P.; Scarsi, M.; Tincani, A.; Merigo, G.; Porteri, E.; Petroboni, B.; Gavazzi, A.; Rosei, C. Agabiti; Castellano, M.; Mori, L.; et al.
Abstract : Objective: Both innate and adaptive immune systems may contribute to the pathogenesis of cardiovascular disease and vascular remodeling through inflammation and oxidative stress. Particularly, the balance between Th1 effector lymphocytes (producing interferon-γ), Th 17 (producing IL-17) and T regulatory (Treg) lymphocytes, which elicit an anti-inflammatory activity, may be crucial for blood pressure elevation and organ damage development, at least in experimental models. Tregs have been previously demonstrated to inversely correlate with subcutaneous small resistance artery media to lumen ratio (M/L) and retinal arteriole wall to lumen ratio (W/L) (unpublished data). Design and method: Therefore, we evaluated the possible relationship between Treg detected in small resistance arteries and circulating levels of Treg. We enrolled 11 normotensive subjects and 4 hypertensive patients undergoing an election surgical intervention (usually removal of adrenal gland for a non-producing adenoma). No sign of local or systemic inflammation was present in any subjects or patients. All patients underwent a biopsy of subcutaneous fat during surgery and small resistance arteries were isolated. We extracted genomic DNA from small resistance arteries and analyzed methylation status of the FoxP3 gene promoter involved in Treg lymphocytes activation. Unmethylated FoxP3 has been demonstrated to be specific for Treg lymphocytes. A peripheral blood sample was obtained before surgery for assessment of T lymphocyte subpopulations. Lymphocyte phenotype was evaluated by flow cytometry after 5 days in vitro activation in order to assess Th17 lymphocytes. Results: A significant positive correlation was detected between Treg in small resistance arteries and circulating levels of Treg (R = 0.42, p∼0.05) whereas an inverse correlation was observed between Th17 lymphocytes and Treg in small resistance arteries (R = -0.46, p < 0.05). Conclusions: Our data suggest that Treg lymphocytes detected in subcutaneous small resistance artery wall are related to circulating Treg which were previously observed to inversely correlate with subcutaneous small resistance artery media to lumen ratio and retinal arteriole wall to lumen ratio. This suggest that Treg may be protective against microvascular damage confirming an involvement of adaptive immune system on microvascular remodeling.